Effect of aging on pulmonary inflammation, airway hyperresponsiveness and T and B cell responses in antigen sensitized and challenged mice - Busse, Paula J. (2007)
BACKGROUND: The effect of aging on several pathologic features of allergic-asthma (pulmonary inflammation, eosinophilia, mucus-hypersecretion), and their relationship with airway hyperresponsiveness (AHR) is not well characterized. OBJECTIVE: To evaluate lung inflammation, mucus-metaplasia and AHR in relationship to age in murine models of allergic-asthma comparing young and older mice. METHODS: Young (6-week) and older (6-, 12- 18-month) BALB/c mice were sensitized and challenged with ovalbumin (OVA). AHR and bronchoalveolar fluid (BALF) total inflammatory cell count and differential were measured. To evaluate mucus-metaplasia, quantitative PCR for the major airway mucin-associated gene, MUC-5AC, from lung tissue was measured, and lung tissue sections stained with periodic acid-Schiff (PAS) for goblet-cell enumeration. Lung tissue cytokine gene expression was determined by qPCR, and systemic cytokine protein levels by ELISA from spleen-cell cultures. Antigen-specific serum IgE was determined by ELISA. RESULTS: AHR developed in both aged and young OVA-sensitized/challenged mice (OVA-mice), and was more significantly increased in young OVA-mice than in aged OVA-mice. However, BALF eosinophil numbers were significantly higher, and lung histology showed greater inflammation in aged OVA-mice than in young OVA-mice. MUC-5AC expression and numbers of PAS+ staining bronchial epithelial cells were significantly increased in the aged OVA-mice. All aged OVA-mice had increased IL-5 and IFN-γ mRNA expression in the lung and IL-5 and IFN-γ protein levels from spleen cell cultures compared to young OVA-mice. OVA-IgE was elevated to a greater extent in aged OVA-mice. CONCLUSIONS: Although pulmonary inflammation and mucus-metaplasia after antigen sensitization/challenge occurred to a greater degree in older mice, the increase in AHR was significantly less compared with younger OVA-mice. Antigen treatment produced a unique cytokine profile in older mice (elevated IFN-γ and IL-5) compared with young mice (elevated IL-4 and IL-13). Thus, the airway response to inflammation is lessened in aging animals, and may represent age-associated events leading to different phenotypes in response to antigen provocation.